Member of Academic Committee - Panigyrakis, George G. (My University, 2026)
Indicatively the PhD theses include: ➢ The influence of culture on luxury consumption. ➢ Advertising Creativity: A Friction Point Βetween Advertising Agencies and Clients. ➢ Colour in Advertising. ➢ Brand Managers’ Profile: a European comparative study. ➢ Entrepreneurial Networks in a globalizing Economy: The Case of Greek Entrepreneurial Networks. ➢ The Value of the Brand: The Case of Luxury Brands. ➢ Electronic Public Relations (E-PR). ➢ Internal Market Orientation, External Market Orientation and Business Performance: The Case of Supermarket Chains. ➢ The efficiency of marketing information systems. The case of hotels in Greece. ➢ The Development of Brand Management Structure and the Organizational Environment. Since 2018, three PhD Thesis are under review, internally.